IMPLEMENTASI PROGRAM BEASISWA BANK INDONESIA DALAM RANGKA MENINGKATKAN KUALITAS PENDIDIKAN DI UNIVERSITAS SUMATERA UTARA - MEILISA KRISTA SHINTA ULI (Welfare StatE, 2013)
The problem of education is an important issue that is facing our nation today. Lack of education in Indonesia can be seen in the Data Release of the Education For All (EFA) Global Monitoring Report 2011: Education Development Index which UNESCO (Education Development Index / EDI) Indonesia in year 2011 is 0.934 value is what puts Indonesia at position 69 of 127 countries in the world. Issues regarding the high cost of education is one of the biggest factors in the decline in the quality of our education today. Due to today there is no doubt that every year, every level of education continues to increase tuition fees, as a result many of them are out of school, because the school was not even deterred problems cost of education. Hence see the importance of education as well as a variety of the many problems facing that could hinder the continuity of educational improvement than this thesis aims to determine how the implementation of the Indonesian bank scholarship program in order to improve the quality of university education in northern Sumatra. This type of research is descriptive research with the population 35 people then the entire population were take data and the data are the recipients of Bank Indonesia, which was at the University of North Sumatra on S1. In this research, data collection techniques used were a literature study is to use the data or information, examine the books, magazines, newspapers, and other writings by the field study with questionnaires and interviews. The questionnaire was distributed to students at North Sumatra University students who receive scholarships of Bank Indonesia. The questionnaire was administered either Such direct (face to face with the scholarship recipient) and indirectly (through the hp telecommunications media and email) is due to some of the scholarship recipients will no longer attend the University of North Sumatra and are out of town in other words the students have graduated from the University of North Sumatra and are now working in their respective fields thereby granting kuisionernya must be done via email or over the phone interview. Based on the results of this research is that scholars Bank Indonesia has a scientific attitude, kekhritisan, creative and high curiosity value of the scholarship program provided by Bank Indonesia. This is evident from the performance, extensive knowledge, could finish study with satisfactory results and enthusiastic community that Bank Indonesia set a goal to establish a communication forum to interact, share inspiration and motivation in a positive, as the container's capacity building in the face of dynamics of community life. Keywords: Scholarship Program, Quality of Education, Higher Education, Scholarship